MicroRNA-146a Overexpression Impairs the Positive Selection during T Cell Development - Li, Zinan; Zhang, Siya; Wan, Ying; Cai, Menghua; Wang, Weiqing; Zhu, Yuli; Li, Zhen; Hu, Yu; Wang, Huaishan; Chen, Hui; Cui, Lianxian; Zhang, Xuan; et al. (Frontiers in Immunology, 2018)
MiRNAs play crucial roles in modulating immune system. MiR-146a, a potent feedback suppressor of NF-κB signaling, was shown to limit the innate immune response and myelopoiesis in a knock-out mouse model. Here, we observed high lymphopoiesis demonstrated as mild splenomegaly and severe lymphadenopathy in a miR-146a transgenic mouse model. Overexpression of miR-146a resulted in enhanced proliferation and reduced apoptosis of T cells. More activated CD4+ T cells or effector memory T cells were observed in transgenic mice even under physiological conditions. Importantly, as one of the key steps to generate central tolerance, the positive selection of thymocytes is impaired in transgenic mice, resulting in more CD4+CD8+ double-positive but fewer CD4+CD8- and CD4-CD8+ single-positive thymocytes. The maturation of selected CD4-CD8+ thymocytes was also impaired, leading to more severe loss of CD4-CD8+ than CD4+CD8- thymocytes in thymus of transgenic mice. Gene expression profiling analysis identified nine positive selection-associated genes which were downregulated in transgenic mice, including genes encoding MHC class I/II molecules, IL-7 receptor α chain and Gimap4, whose downregulation may contribute to the impairment of positive selection. Gimap4 was verified as a novel target of miR-146a. These findings further extend our understanding of the function of miR-146a in T cell biology and identify a novel regulatory mechanism underlying positive selection during T cell development.